1987
DOI: 10.2307/2112271
|View full text |Cite
|
Sign up to set email alerts
|

The Stratification of High School Learning Opportunities

Abstract: This paper suggests that students' opportunities to learn may I , stratified both between and within schools. Schools serving a more affluent and able clientele may offer more rigorous and enriched programs of study, and students in college preparatory curricular programs may have greater access to advanced courses within schools. This notion is tested with a longitudinal, nationally representative sample of public school students from the High School and Beyond data set. The results show few effects of school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
285
2
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(300 citation statements)
references
References 43 publications
4
285
2
9
Order By: Relevance
“…In a large scale study using High School & Beyond survey data, Gamoran (1987) found that while social studies coursework maintains a small effect on achievement test scores, there was little variation in the quantity of coursework completed. His analyses, however, account for neither student performance in the social studies coursework under study, nor the type of social studies coursework taken.…”
Section: Schooling and Citizenship Educationmentioning
confidence: 99%
“…In a large scale study using High School & Beyond survey data, Gamoran (1987) found that while social studies coursework maintains a small effect on achievement test scores, there was little variation in the quantity of coursework completed. His analyses, however, account for neither student performance in the social studies coursework under study, nor the type of social studies coursework taken.…”
Section: Schooling and Citizenship Educationmentioning
confidence: 99%
“…Further authors (e.g., Boudon, 1974) identify the main cause in the insufficient economic resources of lower education families. Another stream of theories (e.g., Gamoran, 1987;Oakes, 2005) approach the issue from a completely different perspective and try to demonstrate that inequality reproduction is built in the education system's organization.…”
Section: Theories Of Education Inequality Reproductionmentioning
confidence: 99%
“…Scheduling constraints can amplify existing tendencies for clustering as schools organize course offerings in terms of tracks and cohorts (Gamoran, 1987;Hallinan and Sorensen, 1985;Nystrand and Gamoran, 1991;Oakes, 1985;Oakes and Guiton, 1995;Sorensen, 1987). That is, because courses offered simultaneously are mutually exclusive, some courses cannot be taken together.…”
Section: Dependencies In Course-takingmentioning
confidence: 99%